2018
DOI: 10.1111/sms.13054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fasted vs fed‐state exercise on performance and post‐exercise metabolism: A systematic review and meta‐analysis

Abstract: The effects of nutrition on exercise metabolism and performance remain an important topic among sports scientists, clinical, and athletic populations. Recently, fasted exercise has garnered interest as a beneficial stimulus which induces superior metabolic adaptations to fed exercise in key peripheral tissues. Conversely, pre-exercise feeding augments exercise performance compared with fasting conditions. Given these seemingly divergent effects on performance and metabolism, an appraisal of the literature is w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 92 publications
2
61
2
7
Order By: Relevance
“…There is little doubt that the investigation of how nutrient intake in and around exercise might modulate the metabolic, molecular and adaptive responses to exercise training is of major current interest (9,10,23,(49)(50)(51) . However, there is a need for further research in order to fully elucidate if overnight-fasted exercise could be a means to optimise the health benefits of physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…There is little doubt that the investigation of how nutrient intake in and around exercise might modulate the metabolic, molecular and adaptive responses to exercise training is of major current interest (9,10,23,(49)(50)(51) . However, there is a need for further research in order to fully elucidate if overnight-fasted exercise could be a means to optimise the health benefits of physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, to avoid any potential confounding by prior food and caffeine ingestion [40,41], we opted to test the participants in a fasted state. This needs to be acknowledged as a limitation given that caffeine supplementation and exercise in a fasted state is likely not a "real-life" practice of many individuals, and is not in line with the current sports nutrition recommendations [42]. Future studies may consider further exploring this topic by using caffeine supplementation protocols that mirror those more commonly observed in practice.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Fasting and fed conditions divergently influence skeletal muscle structure and metabolism [36]. In this study, we found that fasting influenced expressions of Fgfs in mouse skeletal muscle.…”
Section: Discussionmentioning
confidence: 50%